Quality attributes and performance satisfaction of open source library system: A survey amongst librarians in Pakistan - Masrek, Mohamad Noorman; Khan, Asad; Doan, Truong Cong (Malaysian Journal of Library and Information Science, 2022)
Despite its widespread use, KOHA is not without complications. Quality attributes such as functionality, maintainability, user friendliness, and overall performance were frequently identified as issues in empirical studies. While attempts were made to assess the KOHA’s quality attributes, the coverage or scope of the assessment was limited to only a few attributes. Furthermore, the majority of these studies were descriptive in nature, with no theoretical model or framework as a foundation. Given this gap, a study was conducted to assess KOHA’s quality rating and its relationship with overall performance satisfaction. Six research hypotheses were developed and tested in conjunction with an integrated theoretical framework that combined quality attributes and performance satisfaction. A survey using online questionnaire as the data collection technique was administered to librarians or other professionals involved in the implementation of KOHA systems in Pakistan. The study revealed that while quality attributes were not rated highly, they were found to have a significant impact on performance satisfaction. Specifically, functionality, efficiency, maintainability, portability, usability, and reliability are found to have joint influence on performance satisfaction. The findings have made an important contribution from both theoretical and practical perspectives.